2005
DOI: 10.1128/jb.187.11.3848-3854.2005
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the Iron-Sulfur Flavoproteins fromMethanosarcina thermophilaandArchaeoglobus fulgidus

Abstract: Iron-sulfur flavoproteins (ISF) constitute a widespread family of redox-active proteins in anaerobic prokaryotes. Based on sequence homologies, their overall structure is expected to be similar to that of flavodoxins, but in addition to a flavin mononucleotide cofactor they also contain a cubane-type [4Fe:4S] cluster. In order to gain further insight into the function and properties of ISF, the three-dimensional structures of two ISF homologs, one from the thermophilic methanogen Methanosarcina thermophila and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…At the FMN site, the N 5 atom is shielded by a phenylalanine residue, Phe 80, and a similar situation is found in ISF-3 of A. fulgidus, where Phe 84 is found at this position; in the ISF of M. thermophila a methionine, Met 86 provides a potentially more reactive environment (1). In all cases, the roof of the active site cavity is set to interact with aromatics in a stacking interaction between the FMN moiety and Trp 98 in E. coli WrbA, Arg 104 in M. thermophila ISF, and Arg 102 in A. fulgidus ISF-3.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…At the FMN site, the N 5 atom is shielded by a phenylalanine residue, Phe 80, and a similar situation is found in ISF-3 of A. fulgidus, where Phe 84 is found at this position; in the ISF of M. thermophila a methionine, Met 86 provides a potentially more reactive environment (1). In all cases, the roof of the active site cavity is set to interact with aromatics in a stacking interaction between the FMN moiety and Trp 98 in E. coli WrbA, Arg 104 in M. thermophila ISF, and Arg 102 in A. fulgidus ISF-3.…”
Section: Resultsmentioning
confidence: 78%
“…The tetrameric quaternary structure of WrbA of E. coli, as well as of its homologs from D. radiodurans and P. aeruginosa, was first observed in a different family of flavoproteins, the ISFs from M. thermophila and A. fulgidus (1,37). These proteins show the same, typical flavodoxin fold with a fivestranded ␤-␣-␤-topology, but they are characterized by an additional loop region between strand ␤2 and helix ␣2 that contains a compact Cys-X 2 -Cys-X 2 -Cys-X 5 -Cys motif.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies showed that mobile phone addiction could be related or effective on impulsivity and addiction (7), low self-esteem and depression (8), control problems and the symptoms of depression, anxiety and Internet addiction and lower self-confidence (9), high impulsivity, feeling of loneliness and social anxiety (10), extroversion and self-esteem (5), depression, distractibility, lack of tolerance, withdrawal, and escape (11), impulsivity and loneliness (12) and negative consequences such as emotionally-damaged relationships and also reduction of academic achievement (13), family relationship decrease, social isolation, loneliness and depression (7,14); in a study conducted on Hong Kongese youth, psychological characteristics of so-called addiction of mobile phone were identified and four addiction symptoms to mobile phone use were shown such as: loss of control and complaining, anxiety and ravenous and excessive spending habit, withdrawal, neglecting or loss of productivity. The results showed that those who feel mostly fatigue in unemployment times are mostly dependent on mobile phone use and on the contrary the individuals with more self-esteem feel less dependency on or less willing to use a mobile phone (15).…”
Section: Introductionmentioning
confidence: 99%
“…In surveying the BLAST results, it was discovered that several sequences annotated as WrbA contain a motif strictly conserved in another FMN-containing protein family called iron-sulfur flavoprotein (Isf) (2,5,38,39,67). However, the Isf family contains an unusual compact cysteine motif (CX 2 CX 2 CX 5-7 C) that binds a 4Fe-4S cluster not found in the sequences of WrbA proteins or the NQO enzymes aforementioned.…”
Section: Resultsmentioning
confidence: 99%